(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As an impenetrable and highly fortified city, Bharatpur today is known as the ’Eastern Gateway to Rajasthan’ and is an important tourist destination. It was founded in 1733 by Maharaja Suraj Mal. It is famous for its bird sanctuary all over the world Keoladeo Ghana National Park (Baratpur Bird Sanctuary) is a popular tourist attraction and tourist destination in Bharatpur where visitors can see 364 species of birds, 379 species of flowers, 50 species of fish, 13 species of snakes, five species of lizards, species seven aquatic animals, seven species of tortoise and a variety of other invertebrates. All thanks to the tourism of Bharatpur, the park is well maintained and always full of visitors to enjoy the safari. As well as the park, Bharatpur is famous for its various attractions such as Lohagarh Fort, Government Museum, Deeg, Baratpur Palace, Ganga Mandir and many more. With the Tour My India holiday guide to Baratpur, visitors can find all the information about the state such as a great time to visit, activities, attractions and more details. Ornithologist paradise, Bharatpur is also known as Keoladeo Ghana National Park. Bharatpur hosts a vibrant and colorful Brij festival just before the Holi festivities. On their way to Bharatpur, visitors will see the true splendor of Rajasthan.A natural feature of tourism is the quest for authenticity, the desire to experience different cultures in its natural environment in the Bharpur region. Although cultural tourism offers opportunities for understanding and learning, there are negative consequences as a result. It is not just the amount of tourism that is in the workplace, but the types of interactions that occur between tourists and strangers. There are three broad effects at the local level cultural change, the effect of demonstration, and the expansion of another culture in Bharatpur. This Paper provides Information on Tourism in Bharatpur and is a Social Impact.